2017
DOI: 10.1007/s00277-017-3072-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum ferritin is not specific for hemophagocytic lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare, potentially fatal, syndrome of excessive and ineffective activation of the immune system. The majority of the reported data on HLH is from pediatric patients and lacks specificity. This makes HLH diagnosis challenging especially in adults where HLH is triggered by many conditions and can resemble many disease entities. Elevated ferritin is one of the diagnostic criteria for HLH. We determined the conditions associated with elevated ferritin at our medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 20 publications
3
39
1
Order By: Relevance
“…In our case, Brucella-induced haemophagocytic syndrome was suggested by the presence of six of these criteria including fever, splenomegaly, cytopenia (neutropaenia, thrombocytopenia and anaemia), bone marrow haemophagocytosis, hypertriglyceridaemia and hyperferritinaemia exceeding 70 000. HLH was identified in 48.9% of children and 14.2% of adults with ferritin >10 000 µg/L 10. Other factors associated with this syndrome were not examined in our case.…”
Section: Discussionmentioning
confidence: 72%
“…In our case, Brucella-induced haemophagocytic syndrome was suggested by the presence of six of these criteria including fever, splenomegaly, cytopenia (neutropaenia, thrombocytopenia and anaemia), bone marrow haemophagocytosis, hypertriglyceridaemia and hyperferritinaemia exceeding 70 000. HLH was identified in 48.9% of children and 14.2% of adults with ferritin >10 000 µg/L 10. Other factors associated with this syndrome were not examined in our case.…”
Section: Discussionmentioning
confidence: 72%
“…This is problematic for several reasons: first, because the diagnosis of this disease is based on the somewhat arbitrary inclusion criteria for a single clinical trial rather than on any real‐world clinical data; second, because pediatric primary HLH is likely a vastly different disease from adult secondary HLH, and the use of uniform diagnostic criteria for these disparate entities makes little sense; and third, because ferritin, though certainly an exquisite marker of inflammation, is a highly non‐specific one . Notably, HLH‐2004 reported a sensitivity of 84% for their ferritin cutoff however reported no associated specificity …”
Section: Discussionmentioning
confidence: 99%
“…Recently, data have been emerging which call into question the specificity and relevance of several of the HLH‐2004 criteria among adults with suspected secondary HLH . Much of these data have focused on the criterion of serum ferritin, a non‐specific marker of inflammation which, when markedly abnormal, is often a primary driver of HLH workups among hospitalized patients . Studies examining serum ferritin thresholds >3000 ng/mL, 4000 ng/mL, 10 000 ng/mL, and 50 000 ng/mL have demonstrated that hyperferritinemia lacks specificity for HLH .…”
Section: Introductionmentioning
confidence: 99%
“…The criteria largely consist of nonspecific markers of inflammation. These include the findings that are often mistakenly considered more specific for HLH, such as elevated soluble IL2 receptor (sIL2R) and hemophagocytosis . Rubin et al also recently demonstrated that the NK cell cytolytic assay is neither efficient nor reliably diagnostic for primary HLH, with a sensitivity of 60% and a specificity of 72% .…”
Section: Discussionmentioning
confidence: 99%